2021
DOI: 10.3389/fneur.2021.598035
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in Patients With Parkinson's Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Parkinson's disease (PD) and sarcopenia are two common diseases in aging people. To date, the prevalence of sarcopenia in PD patients and the relationship between clinical features and sarcopenia in PD patients are not clear. The aim of the study was to (1) assess the prevalence of sarcopenia in PD patients and (2) reveal the clinical features between PD patients with and without sarcopenia.Method: A systematic review was carried out through screening PubMed, EMBASE, and Cochrane database in May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Sarcopenia, the progressive loss of muscle mass and function [ 64 , 65 ], is prevalent in older adults living with PD and is associated with the severity of the disease [ 66 , 67 ]. In C. elegans , sarcopenia corresponds to a reduction in mobility, which is assessed by counting the number of body bends, or thrashes, in liquid media.…”
Section: Resultsmentioning
confidence: 99%
“…Sarcopenia, the progressive loss of muscle mass and function [ 64 , 65 ], is prevalent in older adults living with PD and is associated with the severity of the disease [ 66 , 67 ]. In C. elegans , sarcopenia corresponds to a reduction in mobility, which is assessed by counting the number of body bends, or thrashes, in liquid media.…”
Section: Resultsmentioning
confidence: 99%
“…low muscle mass and function) may differ according to the diagnostic criteria used, recent pooled analyses revealed that these conditions are highly prevalent among community‐dwelling 3 and hospitalized older adults 4 as well as patients with lung diseases, 5 liver cirrhosis, 6 cancer, 7 and other diseases. 8 , 9 , 10 Patients may also lose muscle in the presence of obesity (i.e. sarcopenic obesity) or without changes in body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease (PD) is the second most common neurodegenerative disease in the elderly [1][2][3][4]. It occurs due to a substantial decrease in dopamine secretion caused by the degeneration of dopaminergic neurons in the substantia nigra pars compacta [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs due to a substantial decrease in dopamine secretion caused by the degeneration of dopaminergic neurons in the substantia nigra pars compacta [5][6][7][8][9]. Skeletal muscle atrophy has been reported in PD [1][2][3][4]. Overexpression of myostatin, a negative regulator of skeletal muscle mass, has been shown in atrophied skeletal muscles [10].…”
Section: Introductionmentioning
confidence: 99%